IRRIGATION TECHNIQUE TO INCREASE THE EFICIENCY OF WATER USE IN TOMATO - López Ordaz, Anselmo; Trejo López, Carlos; Ramírez Ayala, Carlos; Peña Valdivia, Cecilia Beatriz; Tijerina Chávez, Leonardo; Carrillo Salazar, José Alfredo (Revista Mexicana de Ciencias Agrícolas, 2018)
The aim of this research was to study in hydroponics and greenhouse conditions the effect of two levels of usable moisture from the substrate in tomato plants (Solanum lycopersicum L.), by the irrigation technique of partial root drying (PRD). For that, physiological variables were evaluated (dry matter of leaf, stem, root and fruit, water relations, gas exchange, yield), fruit quality (firmness, total soluble solids, pH and electrical conductivity) and the efficiency of water use. The experiment was done in Lomas de San Esteban, Texcoco, Mexico State in 2006. Plants grew in homogeneous volume containers with tezontle, the root was divided in two parts and two available moisture (AM) treatments were applied residual in substrate, control: 80%≤ AM≤ 100% and 80%≤ AM≤ 100% and PRD: 80%≤ AM≤ 100% and 30%≤ AM≤ 100%. The treatments started 28 days after transplantation and continued until the end of the experiment. Results indicated that PRD treatment, showed statistically significant differences (p≤ 0.05) than the control, in relation to CO2 fixation rate (PRD, 17.67 and control 9.23 μmol m-2 s-1) at 86 days of initiating the treatment (DAIT), evapotranspirated volume per plant throughout the experiment (PRD 186.7 L and control 229 L), fruit quality increased: firmness 25%, total soluble solids 13% and electrical conductivity 13%, compared with control; efficiency in water use (EWU) based on dry matter increased by 29% and instantly EWU was 57, 61 and almost 100% respect to the control at 65, 80 and 86 DAIT respectively, without affecting yield (PRD 363.2 g and control 345.8 g) and total water potential (PRD -0.54 and control -0.57; PRD -0.46 and control -0.55 MPa), at 79 and 118 DAIT respectively.
Keywords: Solanum lycopersicum L.; chemical signals; root-shoot communication